Effect of Cluster Acupuncture of Scalp-point combined with Rehabilitation Training for Daily Living Ability of Patients with Parkinson's Disease - Linjing WANG; Yuan TIAN; Chunying WANG; Lu WANG; Lili SHANG; Wei AN; Hong CHANG (康复学报)
Objective:To explore the effect of cluster acupuncture of scalp-point combined with rehabilitation training for daily living ability of patients with Parkinson's disease.Methods:A total of fifty patients with Parkinson's disease were treated in the second affiliated hospital of Heilongjiang university of traditional Chinese medicine were randomly divided into the control group and observation group, with twenty-five cases in each group. The control group was given simple rehabilitation training, loosening-up activities for 10 min a time first, and 30 minutes'Pavel rehabilitation training in preparation period,3 times a week, continuous training for two weeks. During the training period, six movements including leg kicking, leg flexion and extension, chest, rowing, hip and body extension were request, thirty times each movement, sixty minutes for tainning, once every other day, continuous training for four weeks. The observation group was given cluster acupuncture of scalp-point on the basis of the control group. The acupoints from the top area, the front area of the top and suboccipital region were selected, and each area was treated by 3-5 acupuncture needles, acupuncture depth is about 20-25 mm, twisting about 200 turns/min after the needle, continuous twisting for five minutes, which is suitable for patients to tolerate, retaining needle 6-8 h, and carry out rehabilitation training during the period of retaining needle, once a day, five days a week, continuous treatment for six weeks. Before and after the treatment for six weeks, the motor function of the patients was assessed with the Unified Parkinson Disease Rating Scale-Ⅲ(UPDRS-Ⅲ), balance function was assessed by the Fugl Meyer balance function scale, daily living activity was assessed by the Barthel index scale.Results:Before treatment, there was no significant difference in UPDRS-Ⅲ, Fugl Meyer and Barthel scores between the two groups (P>0.05). Compared with treatment before, the UPDRS-Ⅲscores of both groups decreased significantly after treatment for six weeks, Fugl Meyer and Barthel scores increased significantly, with statistical significance (P<0.05). Compared with the control group, UPDRS-Ⅲscores of the observation group were significantly lower, Fugl Meyer and Barthel scores were significantly higher, with statistical significance (P<0.05).Conclusion:Cluster acupuncture of scalp-point combined with rehabilitation training can improve the motor function and balance function of patients with Parkinson's disease, and improve their daily living ability.